Prognostic indicators for papillary thyroid carcinoma. Issue 2 (4th March 2017) - Maino, Fabio; Forleo, Raffaella; Pacini, Furio
ABSTRACT: Introduction : Differentiated thyroid cancer (DTC) includes more than 90% of all thyroid carcinoma and its incidence is growing, mainly due to an increase in the incidence of papillary thyroid cancer (PTC) for the widespread use of neck ultrasonography. Areas covered : Several prognostic factors should be considered during the management of PTC in order to provide the most effective treatment. The most important prognostic factors in PTC include personal and pathological features such as patient's age, gender, hystotype, tumor size, extrathyroidal extension, lymph node involvement, presence of local or distant metastases and molecular analyses. We performed a search in the PubMed database for studies published in English since 1960 using the terms: 'thyroid cancer', 'prognostic factors', 'age', 'gender', 'hystotype', 'tumor size', 'extrathyroidal extension', 'lymph node', 'metastases' and 'molecular analyses'. Expert commentary : Prognostic factors can guide clinicians during the treatment and follow-up of DTC patients, but it is now evident that the risk of recurrence or death must be evaluated periodically, on the basis of individual risk, according to the response to initial therapy or the subsequent therapy required during follow-up.